(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to know how Potato Corner utilizes the existing marketing strategy in terms of product, price, place, and promotion. The results of this study reveal that the employed marketing strategy of Potato Corner is a psychological marketing strategy, franchising strategy, French fries unique flavors, and sales promotion; the utilization of the existing marketing strategy of Potato Corner in Vicas, Caloocan City is “Highly Utilized” in terms of price and place and “Moderately Utilized” in terms of product and promotions; there is a basis for standardization for marketing strategy. This study recommends that Potato Corner should maintain an open door for other characteristics that possibly might be their potential customers. This would be a very successful strategy for Potato Corner to increase its target market and sustainably build its business. To utilize the existing marketing strategies employed at Potato Corner, the researchers recommend continuing to use the 4p’s marketing mix, such as product, price, place, and promotion. Potato Corner should develop its promotions and advertising strategy so that it can reach more potential customers through social media, create some anniversary promotions to increase customer loyalty, and inform potential customers that you have something to offer. Branches of Potato Corner should upgrade the set of standardization that the company implemented to ensure high-quality content and brand consistency of Potato Corner.